An Application of Goal Programming in Data Envelopment Analysis - Venkateswarlu, B.; Mahaboob, B.; Ravi sankar, J.; Narayana, C.; Madhusudhana Rao, B. (International Journal of Engineering and Technology, 2018)
This research paper describes the transformation of the CCR fractional Programming Problem in to the CCR linear programming problem and the dual of the CCR problem. Here the Dual of CCR problem is viewed as BCC [1] formulation Obtained by axiomatic considerations. A goal programming method for finding common weights in DEA with an improved discriminating power for efficiency was proposed by A. Makui et.al [2]. Hamid Reza Babaee Asil and Sara Fanati Rashdi [3] investigated the relationship between resource allocation problems with the problem of weight control and target selection. M. Izadikhah, R. Roostaee et.al [4] proposed a method in which DEA problem can be solved by transforming it into MOLP formulation. The present research study explains the method of finding extremely efficient DMUs and their marveric indexes, the procedure to increase the discriminating power of DEA and the Process of obtaining a set of multiplier weights common to all the DMUs which leads to Global efficiency. In the following discussion a procedure to improve the discriminative power of DEA with goal Programming is proposed.Â Â